GUIDED ENDODONTIC ACCESS IN A CALCIFIED DOUBLE-ROOTED MAXILLARY PREMOLAR: A CASE REPORT - Freire, Luana Costa; Silva Júnior, Roberto Paulino da; Souto, Lucas Rafael do Amaral; Lopes, Mariana Xavier; Cavalcante, Cleiton Felipe Ferreira; Leitão, André Felipe Dutra; Alves, Nayane Chagas Carvalho; Matos, Felipe de Souza (Arquivos de Ciências da Saúde da UNIPAR, 2025)
Root canal treatment in teeth with severe pulp calcification represents a clinical challenge due to the difficulty in locating the canal lumen and the possibility of surgical accidents. This clinical case report aims to describe and discuss a guided endodontic access protocol in a double-rooted tooth with two calcified canals diagnosed with pulp necrosis. Radiographic and cone-beam computed tomography examinations revealed a hypodense image involving the coronal region and cervical root third, severely calcified root canals, and regular apical tissues. Surgical planning software was used to design and 3D-print two guides that directed a #103.395 access bur to the root canal lumen up to the pre-planned depth in the apical third, allowing minimal removal of tooth structure. The endodontic treatment included a single session using ProTaper Ultimate rotary instruments and 2.5% sodium hypochlorite. Passive ultrasonic irrigation with 17% EDTA and saline was performed before obturation. The access cavity was restored. After four months, the tooth was asymptomatic and functioning regularly. The study concluded that guided endodontic access may improves the effectiveness of treating calcified root canals, preserves healthy dental structure, and may reduces surgery time.